PERANAN INTERAKSI GURU DAN SISWA, PERHATIAN ORANG TUA DAN PENYESUAIAN DIRI TERHADAP KENAKALAN REMAJA - SUMIYATUN, SUMIYATUN (2011)
The study was conducted to understand the role of teacher and student interaction, parental attention and adjustment to juvenile delinquency. Subjects in this study were junior high school student A and B Boyolali. The sampling technique used was cluster random sampling technique. The sample in this study as many as three classes with the number of samples used as many as 85 students. Data collection technique using a scale interaction of teachers and students, parental attention, adjustment and juvenile delinquency, while the technique of data analysis using multiple regression analysis. Based on the analysis of data obtained correlation coefficient values F for (F = 12.233, p <0.01)., This suggests that the interaction of teacher and student relationships, parental attention and adjustment to juvenile delinquency proved significant. Then From the coefficient of determination (adjusted R square) is known to 0221. This indicates that the influence of teacher interaction and sisiwa of parental attention and adjustment have the effect of 21.1% and was 79.9% is the influence of other variables outside of this research. Then the contribution of the role of teacher and student interaction on juvenile delinquency by 9.4% (coefficient of determination = 0.094), parental attention 14.6% (coefficient of determination = 0.146) and adjustment of 21.9% (coefficient of determination = 0.219) There is a difference between men with women (F = 3.210, p> 0.05) with the percentage for battery-male students at 54.1% and female students amounted to 45.9%, this suggests boys are more dominant than the students women and differences in age (F = 2.778, p> 0.05) for age 12 years 14%, age 13 years 28%, 40% aged 14 years and to age 15 years 18%. That is between the ages of 12 to 14 years was increasing, but at age 15 the percentage declined, so that may be taken notion that age 15 is early age of identity formation that leads to adult attitudes. Furthermore, of the variables tested that the interaction of teachers and students are correlated with juvenile delinquency shown by the r value of 0.324 and p <0.01. This means that there is a significant correlation between teacher and student interaction with juvenile delinquency, parental Perahtian correlated with juvenile delinquency shown by the r value of 0.372 and p <0.01. This means that there is a significant correlation between parental concern with juvenile delinquency, and self adjustment correlated with juvenile delinquency shown by the r value of 0.370 and p <0.01. This means that there is a significant correlation between adjustments with juvenile delinquency. Thus the role that low teacher and student interaction, parental attention and self-adjustment will result in higher juvenile behavior.